Comparative Transcriptome and Proteome Analysis of Salt-Tolerant and Salt-Sensitive Sweet Potato and Overexpression of IbNAC7 Confers Salt Tolerance in Arabidopsis - Meng, Xiaoqing; Liu, Siyuan; Dong, Tingting; Xu, Tao; Ma, Daifu; Pan, Shenyuan; Li, Zongyun; Zhu, Mingku (Frontiers in Plant Science, 2020)
Salt stress is one of the major devastating factors affecting the growth and yield of almost all crops, including the crucial staple food crop sweetpotato. To understand their molecular responses to salt stress, comparative transcriptome and proteome analysis of salt-tolerant cultivar Xushu 22 and salt-sensitive cultivar Xushu 32 were investigated. The results showed the two genotypes had distinct differences at the transcription level and translation level even without salt stress, while inconsistent expression between the transcriptome and proteome data was observed. A total of 16,396 differentially expressed genes (DEGs) and 727 differentially expressed proteins (DEPs) were identified. Wherein, 1,764 DEGs and 93 DEPs were specifically expressed in the tolerant genotype. Furthermore, the results revealed that the significantly upregulated genes were mainly related to the regulation of ion accumulation, stress signaling, transcriptional regulation, redox reactions, plant hormone signal transduction, and secondary metabolite accumulation, which may be involved in the response of sweetpotato to salt stress and/or may determine the salt tolerance difference between the two genotypes. In addition, 1,618 differentially expressed regulatory genes were identified, including bZIP, bHLH, ERF, MYB, NAC and WRKY. Strikingly, transgenic Arabidopsis overexpressing IbNAC7 displayed enhanced salt tolerance compared to WT plants, and higher catalase (CAT) activity, chlorophyll and proline contents, and lower malondialdehyde (MDA) content and reactive oxygen species (ROS) accumulation were detected in transgenic plants compared with that of WT under salt stress. Furthermore, RNA-seq and qRT-PCR analysis displayed that the expression of many stress-related genes was upregulated in transgenic plants. Collectively, these findings provide revealing insights into sweetpotato molecular response to salt stress and underlie the complex salt tolerance mechanisms between genotypes, and IbNAC7 was shown as a promising candidate gene to enhance salt tolerance of sweetpotato.